The Implementation of Character Education in Indonesian Language Learning in Class VIII UPT SPF SMPN 53 Makassar - Muhammad Akhir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
This study describes the implementation of character education in Indonesian language learning, including planning, implementation, and assessment. This research is descriptive research with a qualitative approach. The subjects of this study were Indonesian language teachers at UPT SPF SMPN 53 Makassar. Data were obtained through interviews, questionnaires, observations, and documentation analysis. The credibility test of the data used in this study is the persistence of observations, and then conclusions are obtained. The results obtained in this study are character education in Indonesian language learning at UPT SPF SMPN 53 Makassar has been implemented both in planning, implementation, and assessment of learning but not all of it has been implemented because it is still in the covid-19 pandemic. At the learning planning stage, the Indonesian language teacher has included character values ​​that will be implemented in learning in the syllabus and lesson plans. The implementation of Indonesian language learning at UPT SPF SMPN 53 Makassar has been quite implemented through online learning via WhatsApp. Assessment of Indonesian language learning includes effective assessment.